Analysis of the Influence of Tension on the Fluctuation of iMCVT - Feng Nenglian; Huang Hongyin; Wang Xiaofeng; Chen Longke; Zhang Xingyu (Jixie chuandong)
The Innovative Movable-teeth CVT（ iMCVT） is a new type of non-friction continuously variable transmission,in the process of transmission,there will be fluctuations in rotational speed and torque. In order to investigate the influence of the tension to the fluctuations of the rotational speed and torque,based on the structure and work principle of iMCVT,the causes of iMCVT fluctuations are analyzed. Based on ADAMS,the dynamics simulation model is built. The effect of tension force on the iMCVT transmission fluctuation is studied by changing the tensioning force of the tensioning device on the metal tooth chain. The simulation results show that when the transmission ratio is 1,increasing the tension force can reduce the fluctuation of the rotational speed,when the tension force reaches a certain value（ about 600 N）,the fluctuation of the rotational speed tends to be stable. On this basis,through the formula to calculate the transmission efficiency curve,and in a certain range,increase the tension can improve the transmission efficiency,too much tension can lead to the decline of transmission efficiency. The results of this study laid the foundation for the control of iMCVT tension.